Sequestration of a non-steroidal anti-inflammatory drug from aquatic media by lignocellulosic material (Luffa cylindrica) reinforced with polypyrrole: Study of parameters, kinetics, and equilibrium. Issue 3 (June 2020) - Khadir, Ali; Negarestani, Mehrdad; Mollahosseini, Afsaneh
Graphical abstract: Highlights: Novel Luffa/polypyrrole composite was synthesized for the first time and used for ibuprofen adsorption/removal. The process was exothermic, feasible, and spontaneous in nature. Pseudo-second-order model and Langmuir isotherm were in keeping with the adsorption data. The maximum monolayer adsorption capacity was 19.157 mg/g. Luffa/polypyrrole proved a significantly better performance and efficiency than raw Luffa. Abstract: Luffa cylindrica (LF) is a plant that has been utilized for water treatment, particularly cationic species; however, in terms of anionic compounds, it owns low applicability. Accordingly, in the current study for the first time, LF was reinforced with polypyrrole (ppy) for the elimination of an emerging contaminant named ibuprofen from aquatic media. The prepared LF/ppy adsorbents were characterized by SEM, BET, FTIR, and XRD. LF/ppy was successfully prepared. The equilibrium time was achieved at 90 min. Lower equilibrium time was found at higher LF/ppy dosages. The agitation speed of 100 rpm revealed the highest removal percentage of 97 %. The initial pH of 5 was the optimum value. By enhancing the temperature from 298 to 323 K, the removal percentage decreased from 97 % to 16 %, revealing the exothermic nature of the adsorption processes. The equilibrium and kinetics data were best described by Langmuir (R 2 = 0.9879) and pseudo-second-order (R 2 = 0.9987) models, respectively, with the maximum monolayer adsorption capacity of 19.157 mg/g. In the case of Dubinin-Radushkevich model, the activation energy was calculated to be 2.5 kJ/mol, and so the removal process followed physical sorption. The results revealed that the removal percentage of LF/ppy was 7.72 times higher than raw LF. Herein, the present investigation clearly proved that the novel low-cost LF/ppy composite is an efficient, promising, and cost-effective choice for the elimination of ibuprofen from aqueous media.